Bioinformatic analysis of the potential common pathogenic mechanisms for gastric precancerous lesions and Helicobacter pylori - Yi, Liufeng; Jiang, Tiantong; Tao, Siyu; Li, Nachuan; Ding, Yuan; Li, Meng; Wang, Shaoli; Liu, Zhen (Frontiers in Gastroenterology, 2025)
ObjectiveGastric precancerous lesions (GPL) represent a critical stage in the progression from gastritis to gastric cancer (GC). Helicobacter pylori (H. pylori) infection is a significant etiological factor exacerbating the inflammatory-cancerous transformation. The host immune status is a central regulatory mechanism for GPL, while persistent H. pylori infection drives changes in the immune microenvironment (IME). However, the potential pathological link between GPL and H. pylori remains unclear. This study aims to identify common differentially expressed genes (DEGs) between GPL and H. pylori using bioinformatics analysis, thereby elucidating their shared pathogenic mechanisms.MethodsDEGs were extracted from GPL datasets (GSE87666) and H. pylori datasets (GSE60427) sourced from the Gene Expression Omnibus (GEO) database through GEO2R and R software. Protein-protein interaction (PPI) networks were generated using the STRING database and analyzed with Cytoscape software to identify hub genes. The diagnostic value of these hub genes was evaluated through Receiver Operating Characteristic (ROC) curves and Area Under the Curve (AUC) analysis, validated with datasets GSE130823, GSE60662, and GSE5081. Immune infiltration analysis of key genes was conducted using the CIBERSORT algorithm and ssGSEA. Gene mutation analysis was carried out using the cBioPortal database, and small molecule drugs were detected using the Connectivity Map (CMap) database.ResultsThe analysis revealed 189 DEGs. Functional enrichment analysis highlighted pathways related to immune system regulation, leukocyte migration and chemotaxis, cytokine-cytokine receptor interaction, and chemokine signaling. Seven hub genes were identified: IL6, FCGR3A, CCL3, CXCR4, CXCL9, CCL4, and CCR1. High AUC values for these hub genes indicated their potential for predicting disease occurrence.ConclusionsThis research identified seven hub genes closely related to GPL and H. pylori, elucidating potential mechanisms of disease progression, particularly emphasizing the roles of the IME and chemokine activity. These findings may provide insights for identifying disease biomarkers, inhibiting the “inflammation-cancer” transformation, and preventing GC. Furthermore, the targets and molecular mechanisms identified in this study require further experimental validation to confirm their therapeutic potential.